The Shiite Pluralistic Position on Human Cloning - Sayyid Hasan Islami Ardekani (Religious Inquiries, 2012)
With regard to human cloning or artificial human reproduction – and contrary to the opinions of Sunni scholars - Shiite thinkers have not held a unified position. After having surveyed a number of Shiite fatwas and analyses on the subject, this essay will classify them into four groups. The first group states that we are granted absolute permission to engage in human cloning; while the second group believes that there is limited permission; the third group argues that cloning as such is primarily permitted but because of its consequences and secondary grounds it is prohibited and unlawful; and the fourth group is of the view that cloning as such and by itself is prohibited and unlawful. In what follows, the author has examined these four views, ending in support of the permission theory.